Cholesterol sulfate limits neutrophil recruitment and gut inflammation during mucosal injury - Morino, Kenji; Kunimura, Kazufumi; Sugiura, Yuki; Izumi, Yoshihiro; Matsubara, Keisuke; Akiyoshi, Sayaka; Maeda, Rae; Hirotani, Kenichiro; Sakata, Daiji; Mizuno, Seiya; Takahashi, Satoru; Bamba, Takeshi; et al. (Frontiers in Immunology, 2023)
During mucosal injury, intestinal immune cells play a crucial role in eliminating invading bacteria. However, as the excessive accumulation of immune cells promotes inflammation and delays tissue repair, it is essential to identify the mechanism that limits the infiltration of immune cells to the mucosal-luminal interface. Cholesterol sulfate (CS) is the lipid product of the sulfotransferase SULT2B1 and suppresses immune reactions by inhibiting DOCK2-mediated Rac activation. In this study, we aimed to elucidate the physiological role of CS in the intestinal tract. We found that, in the small intestine and colon, CS is predominantly produced in the epithelial cells close to the lumen. While dextran sodium sulfate (DSS)-induced colitis was exacerbated in Sult2b1-deficient mice with increased prevalence of neutrophils, the elimination of either neutrophils or intestinal bacteria in Sult2b1-deficient mice attenuated disease development. Similar results were obtained when the Dock2 was genetically deleted in Sult2b1-deficient mice. In addition, we also show that indomethacin-induced ulcer formation in the small intestine was exacerbated in Sult2b1-deficient mice and was ameliorated by CS administration. Thus, our results uncover that CS acts on inflammatory neutrophils, and prevents excessive gut inflammation by inhibiting the Rac activator DOCK2. The administration of CS may be a novel therapeutic strategy for inflammatory bowel disease and non-steroidal anti-inflammatory drug-induced ulcers.